Іван Борковський - дослідник археології храмів та давньої сакральної архітектури Чехословаччини - Левкун, Я. (Схід, 2010)
У статті висвітлюється життєвий шлях І. Борковського, чиє ім'я в часи СРСР замовчувалося, а про нього писали тільки як про чеського археолога, не згадуючи про його галицьке
українське коріння. Досліджується внесок ученого у вивчення археології храмів і давньої
сакральної архітектури Чехїї, аналізуються відкриття І. Борковським залишків костелу Пресвятої Марії Богородиці, двоапсидного храму в Лівому Градці, великі археологічні відкриття
на Празькому градці (нині резиденція Президента Чеської Республіки). Знахідки археологічних пам'яток І. Борковським дали змогу усунути білі плями в середньовічній історії Чехії. This article tells us about the life of Ivan Borkovskiy, whose name was unknown in the USSR period. He was written about as
a Czech archeologist, without mentioning his Galician and Ukrainian origin. Now his contributions are explored, the are: the
contribution in the learning archeology of temples and ancient sacral Czechoslovak architecture, the discovery of the remains
from the Holy Virgin Mary church, the exploring of the church with two apses in the Left Gradec and the largest discoveries in the
Prague Gradec which now became the Residency of the President in the Czech Republic. The findings of the archeological
memorials by Ivan Borkovski gave us a possibility to remove the white spots (unproved facts) in the Medieval Czech History.